Lee Tamahori's Once were warriors - M. Hayes (Law Text Culture, 1995)
As a Pakeha reviewer I find it necessary to hedge this review in opposition to a couple of statements about this film which regularly crop up in reviews and commentaries. Since the film is such a brutal and explicit interrogation of violence within a Maori community, Pakeha reviewers tend to applaud the 'honesty' or 'realism' of the film, which in a way assumes this kind of violence is quite the norm for Maoris. The 'real' Maori is then homogenised as the urban Maori disenfranchised from his or her 'traditional' culture. I don't see myself in a position to declare what I consider 'real' Maori life is like, and critics who, upon viewing a single film, think they have the knowledge to articulate the Maori reality are in a very dubious position. The other common statement is that the film succeeds because it deals with, in the words of a reviewer in The Australian Financial Review, 'the taboo subjects of indigenous representation and domestic violence' (Colbert 1994: 16). Just as the term 'honesty' naturalises Maori society as violent, the term 'taboo' naturalises representation as Pakeha. Indigenous representation in this case is assumed to be of Pakehas representing Maoris, and that is why it is considered such a touchy subject. But Maoris do represent themselves every day, only it is the Pakehas who generally have the luxury to debate the politics of representation. I think part of this film's success is, rather, the ways in which it supersedes this debate by assuming that authority to speak and the control of production of texts do not rely on Pakeha humanist generosity. The film steers away from examining Pakeha representation, which, I think, exposes Pakehas as being not nearly as important in Maori cultural issues as Pakehas would like to think they are.